Urban Expressways: Analysing the Legacy of the Hershey Conference - Canna, Romina (International Planning History Society Proceedings, 2024)
In June 1962, Hershey, Pennsylvania hosted the conference "Freeways in the Urban Setting." The gathering occurred only six years after the enactment of the 1956 Federal-Aid Highway Act, which laid the financial groundwork for the Interstate Highway System. Amidst mounting public discontent and a series of contentious debates, the conference convened with a singular aim: to address the challenges posed by urban expressways in isolation from the broader highway network. Central to the conference's discourse were two primary objectives: the strategic design and placement of urban expressways within city landscapes. These deliberations were underpinned by three critical factors shaping urban evolution: land use patterns, aesthetic considerations, and the integration of multimodal transportation networks. The Hershey Conference was not merely a gathering; it served as a harbinger of change. It served as the hopeful prelude of a new Federal-Aid Highway Act, signed into law by President John F. Kennedy on October 23rd of the same year. This legislative milestone marked the climax of a tumultuous period characterized by widespread protests, accusations of corruption, and entrenched bureaucratic resistance, which had eroded the initial public consensus in favor of the expressway projects. This paper aims to delve into the substance of the Hershey Conference within the broader context of urban planning history. Specifically, it will analyze the conference proceedings against the backdrop of two pivotal events, the 1959 45-49 Resolution in San Francisco and the implementation of the 3C Planning Process, an executive procedure stemming from the 1962 legislation signed by President Kennedy. By contextualizing the Hershey Conference within the larger narrative of urban planning evolution in American cities, this study seeks to shed light on its legacy and contribute to the broader discourse on urban development strategies.